Assembly and preparation for the derivative market: a convenience comparison between financial options and futures with view to the eurex and liffe - Neumann, Arne (2013)
This dissertation conveys a swot-analysis of options and futures, partially based on their fundamentals as described in the appendices, with regards to their convenience for an entry. Further, this convenience comparison is reinforced with a view to two of the world’s biggest derivative exchanges, Eurex and Liffe, and examines them in terms of their product lines, trading volume and transaction fees. All-encompassing, the analysis concludes that futures are the most convenient derivative for an entry on the derivative markets, which the analysis of two derivative exchanges substantiates. Additionally, Eurex slightly favours an entry with futures above Liffe, mainly due to higher trading volume and intercessional transaction fees. Apart from that neutral analysis, the studies of general information such as the comprehension of the market as well as price movements are basic prerequisites for an entry. This leads to the recommendable aspect that the convenience of futures need to be seen from a different angle under certain circumstances or scenarios such as personal preference, the level of risk-tolerance and personal wealth.